Orbital apex cyst: a rare cause of compressive optic neuropathy post-functional endoscopic sinus surgery - Yi, Ni Koh; Shu, Fen Ho; Pathma, Letchumanan; Singh, Harvinder; Embong, Zunaina (Dove Medical Press, 2017)
There are various causes that can lead to compressive optic neuropathy. We present here orbital apex cyst as an unusual cause of compressive optic neuropathy in a 49-year-old male. He presented with 2 weeks painless loss of vision in the left eye with left-sided headache. He had had left functional endoscopic sinus surgery for left nasal polyps 4 years earlier. Magnetic resonance imaging of brain and orbit revealed a left discrete orbital nodule, possibly orbital cyst or mucocele, which was compressing on the left optic nerve. Left eye vision improved markedly from hand movement to 6/36 pinhole 6/18 after initiation of intravenous dexamethasone. A subsequent endoscopic endonasal left optic nerve decompression found the orbital nodule lesion to be an orbital cyst. Marsupialization was performed instead of excision, as the cyst ruptured intraoperatively. Postoperative vision improved to 6/7.5 with normal optic nerve function postoperatively. Possible cause of orbital apex cyst is discussed.